(untitled) (Research, Society and Development, 2022)
The university restaurant (RU) of UFRA serves public servants, students, and others, as long as they have a connection with the university, offering meals during lunch hours, for students the meal is free, which combined with the search for balanced and quality meals, causes greater user demand. Therefore, this study aims to assess the perception of student users in relation to the services provided by the University Restaurant. To this end, a survey-type survey was conducted, using questionnaires structured from statements with a 5-point Likert scale. The questionnaire was applied to 230 student users in the UK, who agreed to participate in the survey, during lunch hours, in the entrance queue. The acquired data were analyzed using Microsoft Excel software, version 2016. The results show dissatisfaction regarding the waiting time, related to the service dimension and the best evaluated satisfactorily was the quality of the complement served along with the main dish, fitting in the dimension, meal (food).